Drawing a computer scientist: stereotypical representations or lack of awareness?. Issue 3 (3rd July 2018) - Pantic, Katarina; Clarke-Midura, Jody; Poole, Frederick; Roller, Jared; Allan, Vicki
ABSTRACT: Stereotypes people hold about computer scientists contribute to underrepresentation in computer science. Perceptions of computer scientists have historically been linked to males and a "nerd" culture, which can lead to lack of interest, particularly for girls. This article presents two studies conducted with two groups of middle schoolers: those who attended our programming camp (Study One) and those who did not (Study Two). After analyzing participants' drawings and two survey questions we found that perceptions youth holds about computer scientists may be improving. Additionally, we found that males (versus females) and those youth who did not attend our camp (versus those who did) tended to have more stereotypical perceptions of computer scientists. With this article, we contribute to the literature on CS stereotypes by examining both positive and negative representations youth had about computer scientists. We also cast light on the lack of awareness about this profession among the youth of this age.